Socioeconomic consequences of the COVID‐19 pandemic for people who use drugs - Walker, Shelley; Dietze, Paul; Higgs, Peter; Ward, B.; Treloar, C.; Stoové, M.; Rathnayake, K.; Doyle, J.; Hellard, M.; Maher, L. (Wiley-Blackwell, 2023)
The COVID-19 pandemic triggered widespread socioeconomic hardship, disproportionately impacting disadvantaged populations. People who use illicit drugs are more likely to experience unemployment, homelessness, criminal justice involvement and poorer health outcomes than the general community, yet little is known about the socioeconomic impacts of the pandemic on their lives. To address this gap in the literature, we conducted in-depth interviews with 76 participants from two cohort studies of people who use illicit drugs (people who inject drugs and/or use methamphetamine) in Victoria, Australia. Findings support claims that pandemic-related Social Security supplementary payments and initiatives to reduce homelessness, although not systemically transforming people's lives, produced temporary relief from chronic socioeconomic hardship. Results also indicate how temporary interruptions to drug supply chains inflated illicit drug prices and produced adverse consequences such as financial and emotional stress, which was exacerbated by drug withdrawal symptoms for many participants. Furthermore, increased community demand for emergency food and housing support during the pandemic appeared to reduce participants' access to these services. Our findings about the unintended consequences of pandemic responses on the socioeconomic lives of a group of people who use illicit drugs provide insights into and opportunities for policy reform to redress their entrenched disadvantage.